Reactive species involved in the regioselective photooxidation of heptamethine cyanines. Issue 11 (18th August 2015) - Nani, Roger R.; Kelley, James A.; Ivanic, Joseph; Schnermann, Martin J.
Abstract : Experimental and computational studies indicate that the photodegradation of heptamethine cyanines proceeds via a regioselective photooxidative C–C cleavage reaction involving singlet oxygen and dioxetane intermediates. Abstract : Heptamethine cyanines are important near-IR fluorophores used in many fluorescence applications. Despite this utility, these molecules are susceptible to light-promoted reactions (photobleaching) involving photochemically generated reactive oxygen species (ROS). Here, we have sought to define key chemical aspects of this nearly inescapable process. Near-IR photolysis of a model heptamethine cyanine leads to the regioselective oxidative cleavage of the characteristic polyene. We report the first quantitative analysis of the major reaction pathway following either photolysis or exposure to candidate ROS. These studies clearly indicate that only singlet oxygen ( 1 O2 ), and not other feasible ROS, recapitulates the direct photolysis pathway. Computational studies were employed to investigate the regioselectivity of the oxidative cleavage process, and the theoretical ratio is comparable to observed experimental values. These results provide a more complete picture of heptamethine cyanine photooxidation, and provide insight for the design of improved compounds for future applications.